(untitled) (UNED Research Journal, 2016)
The biotic composition of many ecosystems is being altered quickly, so there is a growing need to understand ecological processes and maintain their biodiversity. We measured the densities of the herbaceous layer of 30 miniplots (50 cm2) established in three transects (25m x 2m), at the Alberto Manuel Brenes Biological Reserve, San Ramon, Costa Rica. We found that the factors influencing the density of herbaceous cover are pH and the amount of leaf litter.